AUTHENTICITY OF TEACHERâS MADE ASSESSMENT IN YOUNG LEARNER PROGRAMMES - Wulandari, Fitri; Anvaliza, Anvaliza (STKIP Muhammadiyah Pringsewu, 2018)
This study aimed to investigate the authenticity of teacherâs made assessment in elementary schools in Kabupaten Pesawaran. The research design for this study was Descriptive qualitative method. It involved 3 English teachers. The data were collected through documentation, and questionnaires which were analyzed qualitatively. The result of data analysis showed that teachersâ assessment planning, assessment implementation as perceived by teachers and students didnât provide completely. The teachers used traditional type of assessment such as multiple choice tests instead of authentic assessment. The limited knowledge and facilities became the problem of English teacher at elementary school in Pesawaran to implement authentic assessment.Â